Supporting healthy drink choices in remote Aboriginal and Torres Strait Islander communities: a community‐led supportive environment approach. (30th October 2019) - Fehring, Emma; Ferguson, Megan; Brown, Clare; Murtha, Kirby; Laws, Cara; Cuthbert, Kiarah; Thompson, Kani; Williams, Tiffany; Hammond, Melinda; Brimblecombe, Julie
Abstract: Objective : To create supportive environments to reduce sugary drink consumption and increase water consumption by partnering with remote Aboriginal and Torres Strait Islander communities in Cape York. Methods : This paper applied qualitative and quantitative methods to evaluate a co‐designed multi‐strategy health promotion initiative, implemented over 12 months from 2017 to 2018. Outcome measures included changes in community readiness, awareness of the social marketing campaign and changes in drink availability. Changes in store drink sales were measured in one community and compared to sales in a control store. Results : Community readiness to address sugary drink consumption increased in two of the three communities. Awareness of social marketing campaign messaging was high (56–94%). Availability of drinking water increased in all communities. Water sales as a proportion of total drink volume sales increased by 3.1% (p<0.001) while sugary drink volume sales decreased by 3.4% (p<0.001). Conclusions : A multi‐component strategy with strong engagement from local government, community leaders and the wider community was associated with positive changes in community readiness, drink availability and sales. Implications for public health : Partnering with community leaders in the co‐design of strategies to create environments that support healthy drink consumption can stimulate local action and may positively affect drink consumption.